Apoptotic enteropathy caused by antimetabolites and TNF-α antagonists. Issue 7 (10th April 2014) - Soldini, Davide; Gaspert, Ariana; Montani, Matteo; Reineke, Tanja; Rogler, Gerhard; Odze, Robert; Weber, Achim
Abstract : Aims: To investigate whether drugs others than mycophenolic acid and ipilimumab might cause graft-versus-host-like apoptotic enteropathy, the clinicopathological findings in four patients were examined who had developed watery diarrhoea and apoptotic enteropathy (three cases from colon and one case from ileal pouch) after intake of antimetabolites (methotrexate and capecitabine) and/or tumour necrosis factor-α inhibitors (etanercept and infliximab). Methods: The clinical charts, endoscopy reports and intestinal biopsies from all endoscopies were reviewed for all patients. Biopsies were evaluated semiquantitatively for apoptosis of basal crypts, dilated damaged crypts, defined as cystically dilated crypts with flattened degenerated epithelium containing apoptotic debris and few neutrophils, and mucosal architecture. Further, the presence of intraepithelial lymphocytes, chronic inflammatory cells in the lamina propria and mucosal ulcerations was recorded and immunohistochemical analysis for human cytomegalovirus and herpes simplex virus was performed. Results: Endoscopic examination revealed normal mucosa in two patients, whereas the other two showed focal ulcerations. Histological changes included increased apoptosis of basal crypts, the presence of dilated damaged crypts and architecture distortion. In all cases, a temporal association between drug intake and/or dose increase, and onset of diarrhoea, was observed, and no convincing evidence of other potentially underlying causes of colitis/enteritis was found, including infections. Conclusions: Pathologists should be aware of the expanding spectrum of drugs that can cause apoptotic enteropathy, including antimetabolites and tumour necrosis factor-α inhibitors.